Loss probabilities for messages with redundant packets feeding a finite buffer. - Altman, E.
The purpose of this paper is to obtain the distribution of the number of lost packets within a sequence of n consecutive packet arrivals into a finite buffer M/M/1 queue. We obtain explicit expressions for the multidimensional generating function of these probabilities based on a recursive scheme introduced by Cidon et al. (1993). We then analyze the loss probabilities of a whole message, and analyze the effect of adding redundant packets. We show that in both heavy traffic as well as in light traffic conditions, adding redundant packets results in decreasing the message loss probabilities
Keywords: M/M/1 queue; Consecutive packet arrivals; Explicit expressions; Finite buffer; Heavy traffic; Light traffic; Loss packet distribution; Loss probabilities; Message loss probabilities; Multidimensional generating function; Recursive scheme; Redundant packets